REBRANDING PT ARSY TOUR AND TRAVEL SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Sahaja, Achmad Ridho; Fianto, Achmad Yanu Alif; Fahminansih, Fenty (Jurnal Art Nouveau, 2015)
Â Abstract: PT ARSY Tour and Travel is one of a tourism service provider company in Indonesia based in Purwokerto city. As a company that has been running for long time enough in tourism service provider bussiness, is needed to build stong brand image so wich can make brand awareness for of company. From the result is needed to rebranding PT ARSY Tour and Travel trough media campaign wich of creating logo, company profile, corporate power point background, stationery set, magazine advertisement, news paper advertisement, flyer, merchendise, social media planning, cutting sticker car. This Final Task would be fitted with company vision wich more compactness and fresh. In this rebranding plan would be takes some several steps to obtain appropriate results wich is the point for created new brand image of PT ASRY Tour and Travel, it comes from with interviews and observations, collecting data from observation, briefing from the company, and then carried out some brain storming with forum discussing group for the design process. Of the process, will be discovered a keyword that will be used for the reference point to design a media campaign, which is find the theme is A Safe Trip. This concept will be implement to all media campaign wich is logo, company profile, corporate power point background, stationery set, magazine advertisement, news paper advertisement, flyer, merchendise, social media planning, cutting sticker car that can be able to increase customer awareness.Â Keywords: Promotion, Rebranding, PT ARSY Tour and Travel, Brand Awareness, Safe trip.